Azolla - a nitrogen source for rice farmers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Azolla, a small free-floating fern associated with the nitrogen-fixing alga Anabaena azollae, is used by rice farmers in Asia as a natural, low-cost source of fertilizer nitrogen. However, farmers elsewhere in the tropics have not been so ready to...